MALE AND FEMALE CLIENTS OF MEN PROVIDING SEXUAL SERVICES: RESEARCH REPORT - GARDIAN-MIAŁKOWSKA, RENATA (Society Register, 2021)
The aim of the research was to gain knowledge of who the people using sexual services are, why they do it and what their relationship with men offering paid sex looked like. Results show that the people who used sexual services were both men and women of different ages and with different professional status. The main reasons for using paid sex services were: unsatisfactory sexual contact,; a sense of loneliness and being neglected by the life partner, partner’s infertility, heartbreak or betrayal of a partner, problems with finding the right partner, unusual sexual preferences, change of gender and treatment of sex-meetings as a form of entertainment.